CAUSES AND EARLY DIAGNOSIS OF VITAMIN B12 DEFICIENCY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Vitamin B12 deficiency is widespread. Among the population groups at risk are older people, vegetarians, pregnant women, and patients with renal or intestinal diseases. The neurological symptoms of vitamin B12 deficiency are unspecific and can be irreversible. Early detection is therefore important, using the most sensitive and specific markers available. In this research, we will discuss vitamin B12 deficiency, various diagnostic tests, and an algorithm used in the investigation of vitamin B12 deficiency.